Assessment of tapered plastic fiber sensors in the applications of structural health monitoring / Luo Dong - Luo, Dong (2013)
In this thesis, the performances of tapered plastic fiber sensors (TPFSs) were assessed in the application of structural health monitoring—e.g., the monitoring of the early-age hydration process of cement pastes and the detection of vibration and crack in a concrete beam. A mathematical model based on ray-tracing theory was constructed to optimize the geometries of the proposed TPFSs, theoretically. Numerical simulation on the TPFS was carried out, as well as the effects of the geometries, including taper ratio, taper length, and launch angle of the initial ray. The surrounding temperature on the performance of the proposed sensor was also studied numerically. Two sets of sensor configurations were carried out to study the performances of TPFSs, which included different stripped lengths and different diameters. Theoretical and experimental results agreed with each other, and it was found that higher temperature sensitivity of the TPFS can be achieved by combining a longer taper length and lower taper ratio. In the monitoring of the early-age hydration process of cement paste, the TPFSs were used to study the host specimen with different sizes—various cement/water ratios, as well as different ambient temperatures. The sensor characteristics were determined and calibrated by an embedded thermocouple. From the experimental results, the curing temperature and setting time were determined by monitoring the curing temperature as the curing progressed. The curing temperature rose with increasing mould size, decreasing w/c ratio, and increasing ambient temperature. The setting time could be shortened by a smaller specimen size, lower w/c ratio, and higher ambient temperature. The TPFSs also showed the ability for vibration and crack detection in a concrete beam (CB). The natural frequencies’ shift can be precisely determined by TPFSs and accelerometers, which indicate that the CB is damaged. The experimental results also demonstrated that the small diameter of the TPFS achieves a good sensitivity for vibration detection. The experiments for crack detection study were employed in small-scale CBs and full-scale reinforced CBs. The results showed that the TPFSs are capable of detecting the axial strain and the crack initiation in scale-model CBs, as well as the deflection and crack on full-scale reinforced CBs. These findings demonstrated that TPFSs are an ideal solution for the application of structural health monitoring in civil engineering.